Drivers, Motivations, and Barriers in the Creation of Energy Communities: Insights from the City of Segrate, Italy - Anita De Franco; Elisabetta Venco; Roberto De Lotto; Caterina Pietra; Florian Kutzner; Mona Bielig; Melanie Vogel (Energies, 2023)
Energy communities (ECs) are considered significant instruments in the energy transition toward a low-carbon world. Important elements for the creation of ECs are the individual drivers, motivations, and barriers that could stimulate their creation. In this article, we focus on developing an understanding of which aspects favor or slow down the establishment of ECs in the community of Segrate (Italy). From a methodological point of view, the authors present a study based on (i) a preliminary desk analysis, consisting of an extensive and multidisciplinary literature review; (ii) an empirical investigation into the case study of Segrate (a municipality in the Lombardy region, Italy), including energy-related data and geospatial information (i.e., from the census and geographic information system); and (iii) data analysis and the collection of original materials incorporating quantitative and qualitative information (based on online surveys and on-the-spot participatory events) relating to the context. As emerges from the survey, in Segrate (considered a typical European middle-sized city), it is difficult to identify the best physical dimension for ECs: the scale of Segrate’s neighborhoods do not correspond to the EC dimension usually referred to in the literature. In Segrate, the neighborhoods encompass between 4000 and 8000 inhabitants, while existing ECs (with heating systems) cover between 20 and 1200 apartments. Multi-vector ECs are forecastable with 10–20 apartments.